Psychometric Properties of the Brazilian Version of the Friendship Quality Questionnaire in a Community Sample of Children and Early Adolescents - DeSousa, Diogo Araújo; Universidade Federal do Rio Grande do Sul, Porto Alegre, RS, Brazil (2013)
The Friendship Quality Questionnaire (FQQ) is an instrument designed to assess children’s perceptions of qualities of their friendship. The aim of this study was to investigate psychometric properties of the FQQ in a Brazilian community sample of children and early adolescents. Participants were 274 students aged 9-13 years (M = 10.46; SD = 0.81), 52.2% boys, who completed the Brazilian version of the FQQ. Confirmatory factor analysis demonstrated the six-factor original structure of the FQQ fit this sample well after the exclusion of one item related to betrayal. Except for the “Conflict” subscale, all factors presented high positive intercorrelations. The total and subscale scores showed good internal consistency. Girls scored higher on the total score and the “Validation and Caring” and “Intimate Exchange” subscale scores as compared to boys. Our findings suggest the FQQ presented good evidences of validity and reliability to assess friendship quality in Brazilian children and adolescents.